Comparison of Alternative Sequencing of Middle-School Science Curriculum: Classroom Learning Environment and Student Attitudes - Fraser, Barry; Long, C. (James Nicholas Publishers, 2015)
We evaluated the effectiveness of two alternative middle-school science curriculum sequences, namely, a general science model and a topic-specific model (i.e., physics, chemistry, etc.). We also investigated the differential effectiveness of the alternative sequences for two ethnic groups. The sample consisted of 367 grade 8 science students from one U.S. state with a general curriculum and another U.S. state with a topic-specific curriculum. The criteria of effectiveness were dimensions of the classroom learning environment (Personal Relevance, Student Cohesiveness, Teacher Support, Investigation/Involvement, Task Orientation) and Enjoyment of Science. Science was enjoyed more by students following the topic-specific sequence (statistically significant with an effect size of 0.74 standard deviations). Additionally, the general curriculum model was more effective than the specific model for Hispanic students in terms of Task Orientation, but the two alternative curriculum sequences were equally effective for Caucasian students.